Ketahanan Entrepreneur Perempuan pada Masa Pandemi COVID-19 - Gainau, Paskanova Christi; Rawun, Yuli (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2021)
The outbreak of Covid-19 has weakened the performance of micro businesses, especially micro scale women entrepreneurs. Entrepreneurs implement various measures to sustain their businesses through the pandemic. This study aims to examine the factors that influence the performance of micro businesses in the city of Manado, North Sulawesi Province. The study uses the sample of 30 micro businesses collected through questionnaires, observations, and interviews with women entrepreneurs with stratified random sampling technique. The collected data was then analyzed with SmartPLS 3.0 M3. The results found that trust and networks have significant influences on the performance of micro businesses during the crisis. The findings imply that businesses need to establish strong relationships with customers as a mean to building trust and networking to enable businesses to survive in the midst of a crisis. In addition, businesses should also improvise their products in times of crisis to maintain the cash flow.Keywords: women entrepreneur; business performance; trust; smartPLS AbstrakPandemi Covid-19 telah menghambat produktivitas usaha di sektor mikro, tidak terkecuali para pelaku usaha perempuan. Penelitian ini bertujuan menganalisis faktor-faktor yang memengaruhi kinerja usaha sektor mikro di Kota Manado, Sulawesi Utara. Penelitian ini menggunakan sampel yang dipilih secara acak yang terdiri dari 30 pelaku usaha mikro perempuan. Data dianalisis menggunakan SmartPLS 3.0 M3, setelah melalui prosespenyebaran kuesioner, observasi, dan wawancara. Hasil penelitian menemukan bahwa faktor kepercayaan (trust) dan jaringan (network) memiliki pengaruh signifikan terhadap kinerja usaha mikro di masa krisis. Kedua faktor ini sangat penting karena kepercayaan dan jaringan memberikan kemampuan bagi pelaku usaha untuk tetap bertahan di masa krisis. Selain itu, pelaku usaha juga sebaiknya melakukan improvisasi atas produknya dimasa krisis untuk menjaga kelancaran arus kas.